Comparative Analysis of Altman Z - Score, Zmijewski, Fulmer and Ohlson Methods in Predicting Financial Distress: Analisis Komparasi Metode Altman Z - Score, Zmijewski, Fulmer dan Ohlson dalam Memprediksi Financial Distress - Eka Hasanah Ariyati; Nurasik Nurasik (Universitas Muhammadiyah Sidoarjo, 2021)
This study was conducted in order to determine the differences between the Altman, Zmijewski, Fulmer and Ohlson methods in predicting financial distress and to find out which method is the most significant in predicting financial distress in packaging and plastic companies on the Indonesia Stock Exchange. In this study using quantitative research methods. The object of research is packaging and plastic companies on the Indonesia Stock Exchange for the 2016-2019 period. The data used is secondary data, namely financial reports published on the official website of the Indonesia Stock Exchange. The data collection technique used purposive sampling with the number of samples obtained as many as 9 companies. The data analysis technique uses a comparison of the average Kruskal Wallis test on the SPSS 18 application. Based on the results of the study, it shows that there are significant differences between the Altman, Zmijewski, Fulmer and Ohlson methods in predicting financial distress in packaging and plastic companies. And from this research it is known that the Altman method is a method that has the highest average value, which means the most significant method among other methods with a value of 113.69, while the Zmijewski method is 48.31, the Fulmer method is 103.31, and the Ohlson method 24.69.